CORRECTIONAL WORK IN THE DEVELOPMENT OF SPEECH IN PRESCHOOL-AGED CHILDREN WITH MUSCULOSKELETAL CHALLENGES (American Journal of Research in Humanities and Social Sciences, 2024)
This article talks about the types of children's cerebral palsy, their causes, and speech exercises used to eliminate speech defects in them.